Tiered Approach to Resilience Assessment. Issue 9 (25th April 2018) - Linkov, Igor; Fox‐Lent, Cate; Read, Laura; Allen, Craig R.; Arnott, James C.; Bellini, Emanuele; Coaffee, Jon; Florin, Marie‐Valentine; Hatfield, Kirk; Hyde, Iain; Hynes, William; Jovanovic, Aleksandar; et al.
Abstract: Regulatory agencies have long adopted a three‐tier framework for risk assessment. We build on this structure to propose a tiered approach for resilience assessment that can be integrated into the existing regulatory processes. Comprehensive approaches to assessing resilience at appropriate and operational scales, reconciling analytical complexity as needed with stakeholder needs and resources available, and ultimately creating actionable recommendations to enhance resilience are still lacking. Our proposed framework consists of tiers by which analysts can select resilience assessment and decision support tools to inform associated management actions relative to the scope and urgency of the risk and the capacity of resource managers to improve system resilience. The resilience management framework proposed is not intended to supplant either risk management or the many existing efforts of resilience quantification method development, but instead provide a guide to selecting tools that are appropriate for the given analytic need. The goal of this tiered approach is to intentionally parallel the tiered approach used in regulatory contexts so that resilience assessment might be more easily and quickly integrated into existing structures and with existing policies.